Evolutionary dynamics in plastomes and mitogenomes of diatoms - Aimee Caye G. Chang; Mailor W. W. Amaral; Megan Greenwood; Catherine Ikudaisi; Jingchun Li; Sarah E. Hamsher; Scott Miller; Patrick Kociolek (PLoS ONE, 2025)
Diatoms are pivotal in global oxygen, carbon dioxide, and silica cycling, contributing significantly to photosynthesis and serving as fundamental components in aquatic ecosystems. Recent advancements in genomic sequencing have shed light on their evolutionary dynamics, revealing evolutionary complex genomes influenced by symbiotic relationships and horizontal gene transfer events. By analyzing publicly available sequences for 120 plastomes and 70 mitogenomes, this paper aims to elucidate the evolutionary dynamics of diatoms across diverse lineages. Gene losses and pseudogenes were more frequently observed in plastomes compared with mitogenomes. Overall, gene losses were particularly abundant in the plastomes of Astrosyne radiata, Toxarium undulatum, and Proboscia sp. Frequently lost and pseudogenized genes were acpP, ilv, serC, tsf, tyrC, ycf42 and bas1. In mitogenomes, mttB, secY and tatA genes were lost repeatedly across several diatom taxa. Analysis of nucleotide substitution rates indicated that, in general, mitogenomes were evolving at a more rapid rate compared to plastomes. This is contrary to what was observed in synteny analyses, where plastomes exhibited more structural rearrangements than mitogenomes, with the exception of the genus Coscinodiscus and one group of species within Thalassiosira.